Hukum Perkawinan Berbeda Kasta Dalam Perspektif Hukum dan Hak Asasi Manusia - I Wayan Sumartika; Diah Gayatri Sudibya; Ni Made Puspasutari Ujianti (Fakultas Hukum Universitas Warmadewa, 2019)
Marriage as a legal problem will raise concerns for husbands in marriage. The philosophical problem, namely the marriage penalty of different castes is contrary to the Almighty values of the Almighty God in Pancasila. Sanctions are discharged (discharged) outside the area and sanctioned by the patiwangi ceremony. The juridical issue, the implementation of sanctions and the patiwangi ceremony in the marriage of different castes should be canceled because it is not in accordance with the Constitution. The method used is normative legal research based on proposed norms or evaluations or real problems, and legal materials obtained will be predicted. The results of the study indicate that there are sociological problems in different caste marriages, where the community still carries sanctions on customary law. The sanctions approved were those issued regarding the elimination of racial and ethnic discrimination or according to national law, there were no agreed provisions regarding the prohibition of the influence of different caste marriages. So as long as this marriage meets the requirements stated in the marriage law, it can be approved legally. Marriage is different depending on the women. According to the Act, every one who discriminates against others forms everything.